Psychology's renaissance. - Nelson, Leif D.
In 2010?2012, a few largely coincidental events led experimental psychologists to realize that their approach to collecting, analyzing, and reporting data made it too easy to publish false-positive findings. This sparked a period of methodological reflection that we review here and call Psychology's Renaissance. We begin by describing how psychologists? concerns with publication bias shifted from worrying about file-drawered studies to worrying about p-hacked analyses. We then review the methodological changes that psychologists have proposed and, in some cases, embraced. In describing how the renaissance has unfolded, we attempt to describe different points of view fairly but not neutrally, so as to identify the most promising paths forward. In so doing, we champion disclosure and preregistration, express skepticism about most statistical solutions to publication bias, take positions on the analysis and interpretation of replication failures, and contend that meta-analytical thinking increases the prevalence of false positives. Our general thesis is that the scientific practices of experimental psychologists have improved dramatically. -- (from the author)